ER/AR Multi-Conformational Docking Server: A Tool for Discovering and Studying Estrogen and Androgen Receptor Modulators - Wang, Feng; Hu, Shuai; Ma, De-Qing; Li, Qiuye; Li, Hong-Cheng; Liang, Jia-Yi; Chang, Shan; Kong, Ren (Frontiers in Pharmacology, 2022)
The prediction of the estrogen receptor (ER) and androgen receptor (AR) activity of a compound is quite important to avoid the environmental exposures of endocrine disrupting chemicals. Estrogen and Androgen receptor database (EARDB, http://eardb.schanglab.org.cn/) provides a unique collection of reported ERα, ERβ or AR protein structures and known small molecule modulators. With the user uploaded query molecules, molecular docking based on multi-conformations of a single target will be performed. And the 2D similarity search against known modulators is also provided. Molecules predicted with low binding energy or high similarity to known ERα, ERβ or AR modulators may be potential endocrine disrupting chemicals or new modulators. The server provides a tool to predict the endocrine activity for compounds of interests, especially forbenefiting for ER and AR drug design and endocrine disrupting chemicals identificationenvironmental exposures.